Critical analysis of constructive dismissal in South African employment law : issues and perspectives - Molepo, Moses Ranti (My University, 2024)
In common parlance employment relationship can be terminated by either the employer or the employee. Termination of employment by the employee is referred to as resignation and termination by the employer’s conduct is defined as constructive dismissal. Dismissal with particular reference to section 186(e) of the Labour Relations Act 66 of 1995 (‘the LRA’) forms the main subject of this study. The above-mentioned section fully explains dismissal to include a position where an employee resigns due to the conduct of the employer who made continued employment intolerable. This dissertation explores decided case laws and various labour legislations related to constructive dismissal. Furthermore the study considers and describes the forms of behaviour that have been and those that will be considered by the courts to be offensive conduct on the part of the employer, and to what end these can be said to necessitate a case of constructive dismissal. The study also looks at definition of constructive dismissal, definition of intolerable conduct of the employer and test to determine constructive dismissal.
Thesis (LLM. Development and Management Law)) -- University of Limpopo, 2024
Keywords: Employer; constructive dismissal; Intolerable conduct; Employee; Stress; Resignation; Grievance; Subordinates; Harassment.; Employees -- Dismissal of -- Law and legislation -- South Africa; Labor laws and legislation -- South Africa; Labor laws and legislation -- South Africa; Employees -- Resignation